2015
DOI: 10.1164/rccm.201409-1587oc
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Metabolic Dysregulation, and Pulmonary Function among Obese Urban Adolescents with Asthma

Abstract: Rationale: Insulin resistance and low high-density lipoprotein (HDL) are associated with pulmonary morbidity, including asthma, but the underlying mechanisms are not well elucidated.Objectives: To investigate whether systemic inflammation underlies the association of metabolic abnormalities with pulmonary function among urban adolescents.Methods: Th-cell responses and monocyte subsets, and their association with serum homeostatic model assessment of insulin resistance (HOMA-IR) and HDL, and pulmonary function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
176
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(200 citation statements)
references
References 51 publications
10
176
0
2
Order By: Relevance
“…128 Recent studies have found that insulin resistance mediates the association of systemic Th1 polarization with obesity-mediated pulmonary function deficits among ethnic minority children. 103 Given these initial investigations into the association among insulin resistance, inflammation, and pulmonary function impairment, further study of the underlying immunometabolic pathways is needed to determine the mechanism through which insulin resistance contributes to the obese asthma phenotype.…”
Section: Association With Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…128 Recent studies have found that insulin resistance mediates the association of systemic Th1 polarization with obesity-mediated pulmonary function deficits among ethnic minority children. 103 Given these initial investigations into the association among insulin resistance, inflammation, and pulmonary function impairment, further study of the underlying immunometabolic pathways is needed to determine the mechanism through which insulin resistance contributes to the obese asthma phenotype.…”
Section: Association With Insulin Resistancementioning
confidence: 99%
“…34 There is preliminary evidence to suggest that this effect may be mediated in part by the protective effect of HDL on monocyte activation. 103 There is also increasing evidence to suggest that the origins of the association of diet-induced metabolic dysregulation and pulmonary morbidity may start as early as in utero. For instance, altered fat intake, with low intake of poly-unsaturated fatty acids in the mother, has been associated with an increased predisposition to asthma among the offspring.…”
Section: Association With Dyslipidemiamentioning
confidence: 99%
“…This clearly suggests that obesity has a direct impact on lung function, and is associated with pathophysiology of asthma. Nonetheless, it also appears that insulin resistance may induce structural changes in the lungs besides driving the inflammatory invasion in lungs 12,13 . Such changes are also known to be associated with metabolic syndrome 14 .…”
Section: Insulin Resistance and Asthmamentioning
confidence: 99%
“…This clearly suggests that obesity has a direct impact on lung function, and is associated with pathophysiology of asthma. Nonetheless, it also appears that insulin resistance may induce structural changes in the lungs besides driving the inflammatory invasion in lungs 12,13 . Such changes are also known to be associated with metabolic syndrome 14 .…”
Section: Insulin Resistance and Asthmamentioning
confidence: 99%